PENGAWASAN DPRD TERHADAP PELAKSANAAN PERDA NO. 13 TAHUN 2011 TENTANG RENCANA TATA RUANG WILAYAH KOTA BEKASI (Studi Tentang Ketersediaan Ruang Terbuka Hijau di Kota Bekasi) - Yohanes Oci; Utang Suwaryo; Aos Kuswandi (Governance, 2022)
This research is motivated by the idea the controlling of Perda No.13/2011 on the Spatial Plan of Bekasi Regency has not been optimal in terms of the achievement of Green Open Space in Bekasi City, West Java Province. The method used in this research is a descriptive analysis with a qualitative approach. The author uses observation techniques, in-depth interviews and transfers basic information to sources who are determined based on purposive sampling, the aim is to obtain the necessary information and data in accordance with the research variables.The results showed that: (1) The program was not achieved in accordance with the provisions as a result of the DPRD not carrying out optimal controlling functions. (2) DPRD does not show maximum integrity in carrying out its supervisory function on the implementation of Spatial Plan of Bekasi Regency regulations and the Spatial Planning Law regarding the achievement of Green Open Space in Bekasi City. (3) The Bekasi City DPRD has been carrying out its regulatory function well, which is proven to be making local regulations on Spatial Plan of Bekasi Regency where the availability of green open space is relevant to the provisions in the Spatial Planning Law, which is 30%, but the achievement of green open space currently still ranges from 11.29%. due to a lack of optimal controlling.